2014
DOI: 10.1097/01.tp.0000435702.61642.0a
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Rejection Associated with Antiviral Therapy for Recurrent Hepatitis C after Living-Donor Liver Transplantation

Abstract: CR developed in association with antiviral therapy for recurrent hepatitis C after LDLT. This complication may be prevented by ensuring that the immunosuppressant dose is not reduced during antiviral therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…reported that seven of 125 (6%) patients developed chronic rejection during or within 6 months after the end of antiviral therapy. In five patients, rejection progressed rapidly and resulted in death within 3 months after diagnosis . On the other hand, plasma cell hepatitis induced by antiviral therapy for recurrent hepatitis C after LDLT .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…reported that seven of 125 (6%) patients developed chronic rejection during or within 6 months after the end of antiviral therapy. In five patients, rejection progressed rapidly and resulted in death within 3 months after diagnosis . On the other hand, plasma cell hepatitis induced by antiviral therapy for recurrent hepatitis C after LDLT .…”
Section: Discussionmentioning
confidence: 98%
“…In five patients, rejection progressed rapidly and resulted in death within 3 months after diagnosis. 31 On the other hand, plasma cell hepatitis induced by antiviral therapy for recurrent hepatitis C after LDLT. 32,33 Although it is important that SVR induced by IFN therapy improved survival rate in patients with recurrent post-LDLT HCV infection, IFN therapy may be recommended in these patients while we are careful of chronic rejection and plasma cell hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…However, IFN‐mediated graft dysfunction is a significant clinical problem that warrants particular caution following living donor LT . Moreover, it was reported that IFN‐based antiviral therapy for recurrent hepatitis C after living donor LT had the potential for causing plasma cell hepatitis and chronic rejection . Therefore, for such difficult‐to‐treat post‐LT patients, IFN‐free daclatasvir and asunaprevir combination therapy will likely be a standard therapy …”
Section: Discussionmentioning
confidence: 99%
“…65 Several uncontrolled studies have suggested that CR may be related to IFN-based therapy (incidence range 4-17%). 64,66 CR is generally detected after one year of therapy and is often observed concurrent with the absence or low levels of hepatitis C viremia. Notably, the majority of patients had not experienced ACR during treatment and yet evolved to CR.…”
Section: Rejection and Autoimmune Complicationsmentioning
confidence: 99%
“…64 It should be noted that IFN-related CR may be partly preventable by ensuring that the immunosuppressant dose is not reduced during antiviral therapy. 66 Autoimmune hepatitis (AIH)-like hepatitis after LT has been reported in HCV patients, particularly with IFN-based therapy. 19,64,67 The histological hallmarks can somewhat resemble classical AIH, including plasma cell-predominant periportal infiltrates with interface hepatitis or so called plasma cell-rich hepatitis.…”
Section: Rejection and Autoimmune Complicationsmentioning
confidence: 99%